The TRIPS Agreement and the Pharmaceutical Industry in India. (January 2020) - Kamiike, Atsuko
The World Trade Organization's (WTO's) Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS Agreement) calls for the harmonization of intellectual property rights (IPRs) regulations across all WTO member countries. The TRIPS Agreement requires all WTO member countries to adopt and enforce minimum standards of intellectual property. It was assumed that the introduction of pharmaceutical product patents would hamper the Indian pharmaceutical industry's growth. Contrary to expectations, however, the Indian pharmaceutical industry has been growing in the post-TRIPS period. The TRIPS Agreement changed the research and development (R&D) orientation of Indian pharmaceutical companies, which have increased their R&D investments. Since the TRIPS Agreement was signed, the pharmaceutical global value chain (GVC) has been re-structured and has now expanded to emerging countries like India. Indian pharmaceutical firms have thus been participating in the pharmaceutical GVC in the post-TRIPS period. This participation is conducive to technological upgrading and technology transfers. While operating in the GVC, Indian pharmaceutical firms are upgrading by adopting state-of-the-art technologies. This study explores how the TRIPS Agreement is influencing the Indian pharmaceutical industry and discusses the industry's growth factors in the post-TRIPS period within the GVC framework. JEL: L21, L24, L26, L65